Siberia and the Far East in the Project “The Map of Bookstores in Russia” - O. N. Alshevskaya; S. Yu. Zorina; A. V. Bezumatova (Библиосфера)
Assessing the state of the bookselling infrastructure by creating an interactive map of the country’s bookstores in order to identify the potential for its development and search for ways to optimize it is an important factor in improving the information exchange of the book industry. The article analyzes the results of the first stage (2023) of monitoring bookselling enterprises in the Siberian-Far Eastern region within the framework of the project “The map of bookstores of Russia” (“The Cultural Map of Russia. Literature. Reading”). The research methodology is based on a combination of comparative typological analysis of monitoring data and the landscape-reconstructing approach. Statistical data on the number of bookselling facilities and their availability in federal districts and cities of Russia are summarized. The information on the location and number of bookselling facilities in the cities of Siberia and the Far East is studied in detail, leaders and outsiders are identified. The representation of federal, regional, and local network formations and independent bookstores in the region is considered. The activities of leading enterprises operating in the region for many years and recently opened bookstores are evaluated. The all-Russian trends and regional features of the development of the bookselling infrastructure are determined. The analysis of monitoring data for bookselling facilities in Siberia and the Far East showed the following. The modern regional bookselling infrastructure, along with its inherent all-Russian features, is characterized by: expansion and strengthening of the position of the federal bookselling network “The City of Read”; significant growth of the Internet channel due to the ongoing consolidation of the main players and the growing popularity of marketplace platforms. At the same time the bookselling infrastructure has a number of regional features. They are the reduction in the activities of the oldest regional network formations, successful adaptation and expansion of local large and medium-size network formations; the emergence and successful operation of special children’s bookstores-clubs, as wekk as club-backroom format stores.